Concentrations and patterns of polychlorinated naphthalenes in urban air in Beijing, China. (November 2016) - Xue, Lingnan; Zhang, Lifei; Yan, Yan; Dong, Liang; Huang, Yeru; Li, Xiaoxiu
Abstract: Air samples were collected, using a high-volume air sampler, at an urban site in Beijing from April 2014 to March 2015. The polychlorinated naphthalene (PCN) concentration in the atmosphere in each season was determined. The total PCN (total target tri- to octachloronaphthalene congeners) concentrations were 1.99–19.0 pg/m 3, and the mean was 7.20 pg/m 3 . The PCN concentrations were higher in fall than summer, indicating that the concentrations varied significantly over time. The trichloronaphthalene homolog was the predominant PCN homolog in all four seasons. The PCN toxic equivalent (TEQ) concentrations were 0.42–6.89 fg/m 3, and the mean was 1.74 fg/m 3 . The CN-66/67 and CN-73 congeners were the predominant contributors to the TEQ concentrations. The mean seasonal TEQ concentration decreased in the order fall (3.18 fg/m 3 ) > winter (1.41 fg/m 3 ) > summer (1.11 fg/m 3 ) > spring (1.03 fg/m 3 ). The TEQ concentrations and the PCN concentrations did not follow the same seasonal trends, but the highest TEQ and PCN concentrations were both found in fall. Correlation analysis, ratio analysis, and principal component analysis were used to investigate the sources of PCNs to the Beijing atmosphere. The results suggested that combustion processes may be the main sources of PCNs to the Beijing atmosphere. Graphical abstract: Highlights: Tri–octachloronaphthalenes in air in Beijing were measured from Apr 2014 to Mar 2015 Polychlorinated naphthalene concentrations were highest in fall. Trichloronaphthalenes were the predominant polychlorinated naphthalenes. The main contributors to polychlorinated naphthalene toxicity were CN-66/67 and CN-73. Combustion processes were the main sources of polychlorinated naphthalene emissions.